Effect of density on Mediterranean pine seedlings using the Nelder wheel design: analysis of survival and early growth. (23rd July 2022) - Ruano, Irene; Pando, Valentín; Bravo, Felipe
Abstract: There is growing interest in mixed-species forests but also a lack of studies that analyse them at the regeneration phases or any stage other than mature stands. Information is particularly scarce about relatively unproductive species such as Pinus pinaster and Pinus halepensis in Mediterranean ecosystems. The objective of this study was to investigate inter- and intra-specific interactions of both species at different tree densities during the first years of establishment. Five Nelder wheel plots were planted to test densities ranging from 1000 to 80 000 seedlings/ha and simulate establishment sub-processes at high densities. Further, P. pinaster and P. halepensis were mixed along the spokes, to obtain three mixture levels in which 100, 80 or 60 per cent of the seedlings were of the same species. Cox proportional-hazards models and binomial logistic regressions were fitted to analyse seedling survival. Early growth (basal diameter and height at one and four years after plantation) was analysed by fitting linear mixed-effects models. In this regard, P. halepensis showed higher survival rates and basal diameter increments but more time is needed to know how P. pinaster responds to density and mixture. Both competitive and facilitating seedling interactions were observed at higher densities, which fostered seedling survival but decreased early growth.